Value of a draft pick : Analysis of the Ontario Hockey League priority selection - Cocker, S. (Haaga-Helia University of Applied Science, 2018)
In majority of professional sports the draft is a core component in building the framework of success for your organization. Successful drafting equals long-term success as it gives an opportunity to add youth and promise to the depth chart. On the other side, poor drafting or mishandling of draft picks in transactions can lead to many years of a poor product on the field of play.